Minimum wage policy in Ireland - Paul Redmond (The Economic and Social Research Institute (ESRI), 2020)
I provide an overview of minimum wage policy in Ireland over the past 20 years, and survey the recent evidence on the economic impacts of a minimum wage. Drawing on this evidence, I analyse the potential implications of the recent Covid-19 crisis on minimum wage employment in Ireland. The recent evidence shows that minimum wage increases in Ireland have not led to increased job loss among minimum wage workers, but have resulted in some reductions in hours worked among certain groups. Minimum wage increases have led to reductions in wage inequality and the minimum wage has been shown to be important in keeping wage inequality low during recessions. Recent estimates show that more than half of minimum wage employees in Ireland work in the retail, accommodation and food sectors. These sectors have experienced widespread business closures due to the Covid-19 crisis, suggesting that low-wage employees may be disproportionately impacted by job losses. Those who have lost their job may claim the Pandemic Unemployment Payment (PUP) of exteuro350 per week. Minimum wage employees in retail or accommodation and food work, on average, 23 hours per week. This means that the PUP payment is 50 per cent higher than the gross weekly wage of the average minimum wage employee in these sectors. However, the PUP payment was an emergency short-term (12-week) measure, and it seems likely that it will be amended or tapered in coming weeks to address these types of anomalies.
Keywords: 330; Mindestlohn; Wirkungsanalyse; Coronavirus; Wirtschaftskrise; Beschäftigungseffekt; Irland